Autosomal dominant retinitis pigmentosa with apparent incomplete penetrance: a clinical, electrophysiological, psychophysical, and molecular genetic study. Issue 8 (August 1993) - Moore, A T; Fitzke, F; Jay, M; Arden, G B; Inglehearn, C F; Keen, T J; Bhattacharya, S S; Bird, A C
Abstract : Twenty five symptomatic individuals and six asymptomatic obligate gene carriers from four families with autosomal dominant retinitis pigmentosa (adRP) showing apparent incomplete penetrance have been studied. Symptomatic individuals from three families showed early onset of night blindness, non-recordable rod electroretinograms, and marked elevation of both rod and cone thresholds in all subjects tested. In the fourth family, there was more variation in the age of onset of night blindness and some symptomatic individuals showed well preserved rod and cone function in some retinal areas. All asymptomatic individuals tested had evidence of mild abnormalities of rod and cone function, indicating that these families show marked variation in expressivity rather than true non-penetrance of the adRP gene. No mutations of the rhodopsin or RDS genes were found in these families and the precise genetic mutation(s) remain to be identified.